Strategic Management of the Quality Control Group (GKM) in Preparing Program Study Accreditation at the Faculty of Teacher Training and Education, Widya Gama Mahakam University, Samarinda: Strategic Management of the Quality Control Group (GKM) in Preparing Program Study Accreditation at the Faculty of Teacher Training and Education, Widya Gama Mahakam University, Samarinda - Prilia Putri, Aldila; Gede Mulawarman, Widyatmike; Bahzar, Moh; Azainil, Azainil; Hidayanto, Dwi Nugroho; Akhmad, Akhmad (Borneo Educational Journal (Borju), 2025)
Strategic management of the Quality Control Circle (QCC) is a quality control approach that emphasizes active participation, collaboration, and creativity of group members in systematically and continuously solving quality problems to achieve improvements in work quality and organizational productivity. The QCC is responsible for carrying out the quality assurance process, primarily through monitoring, evaluation, and control of the implementation of education and teaching, with the main objective of achieving the quality standards set by the educational institution. The purpose of this study is to describe and analyze the management strategy of the Quality Control Circle (QCC) in optimizing the preparation for study program accreditation at the Faculty of Teacher Training and Education, Widya Gama Mahakam University Samarinda. The research focuses on four managerial aspects: planning, organizing, implementation, and supervision in the context of quality improvement through the QCC strategy. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation involving relevant parties, such as faculty leaders, lecturers, and the QCC team. The results of the study show that: 1) The QCC strategy in preparing for accreditation at the Faculty of Teacher Training and Education, Widya Gama Mahakam University Samarinda begins with planning based on SWOT analysis, resulting in a targeted work plan for improving the quality of the study program. 2) Organization is carried out participatively with a clear structure, involving lecturers, staff, and students according to their competencies. 3) Implementation has proven effective through improvements in learning quality, utilization of technology, and the involvement of all faculty elements, which are evaluated using the PPEPP cycle and accreditation achievement indicators. 4) Supervision is conducted through regular evaluation, internal quality audits, and follow-up actions, ensuring that the QCC strategy remains adaptive to changing standards and is able to address the challenges of educational quality in a sustainable manner.